(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
When the Zoroastrian religion, based on the belief of the only deity in Movarounnahr, Iran, Khorasan, was adopted, the construction of a special temple-ceasefire, in which the Ahura Mazda cult sanctuaries were located in the cities and villages of these territories, was in full swing